2010
DOI: 10.1103/physrevb.82.134508
|View full text |Cite
|
Sign up to set email alerts
|

Shot noise and Coulomb effects on nonlocal electron transport in normal-metal/superconductor/normal-metal heterostructures

Abstract: We argue that Coulomb interaction can strongly influence non-local electron transport in normalsuperconducting-normal structures and emphasize direct relation between Coulomb effects and nonlocal shot noise. In the tunneling limit non-local differential conductance is found to have an S-like shape and can turn negative at non-zero bias. At high transmissions crossed Andreev reflection yields positive noise cross-correlations and Coulomb anti-blockade of non-local electron transport.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In Ref. 30, a quasiclassical analysis using a perturbative expansion in the nonlocal Green's function connecting the two interfaces led to positive noise correlations at high transparencies, and the authors conclude that it is due to CAR. This interpretation looks surprising, given the domination of EC in the conductance in the same regime, and the total absence of CAR at high transparency in the transmission coefficient.…”
Section: Introductionmentioning
confidence: 96%
“…In Ref. 30, a quasiclassical analysis using a perturbative expansion in the nonlocal Green's function connecting the two interfaces led to positive noise correlations at high transparencies, and the authors conclude that it is due to CAR. This interpretation looks surprising, given the domination of EC in the conductance in the same regime, and the total absence of CAR at high transparency in the transmission coefficient.…”
Section: Introductionmentioning
confidence: 96%
“…26,27 Recently the effect of Coulomb interaction has been studied in some of these systems. 28,29 On the experimental side, noise experiments with normal superconducting devices constitute a real challenge. A successful experiment demonstrated that the Fano factor of a single NS junction is 2, corresponding to the charge of a Cooper pair.…”
Section: Introductionmentioning
confidence: 99%
“…(13) This in turn allows us to write the full vertex functionˇ by self-consistently solving the Bethe-Salpeter equation in the corresponding irreducibility channel [see Fig. 1(b)]:…”
Section: Kadanoff-baym-keldysh Formalismmentioning
confidence: 99%
“…[7][8][9] Several theoretical works have suggested different directions in order to provide preferential enhancement of CAR, from simple spin and energy filtering to the effect of strong electron interactions, susceptible to favor single-particle over pair tunneling. [10][11][12][13][14] An important step in the observation of Cooper-pair splitting came from recent experimental works in tunable double quantum dot devices based on carbon nanotubes 15 and InAs nanowires. 16 These systems showed great promise, as they not only display local Coulomb repulsion on the dots, but also allow for the exploration of different energy configurations of the dots, two properties that should promote CAR over other processes.…”
Section: Introductionmentioning
confidence: 99%